Simulation methods for preparation of financial plan and business valuation using the DCF method - Zalygin, Vladislav; Poborský, František; Hrdý, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This thesis explores the application of simulation methods, specifically the Monte Carlo method, in the preparation of financial plan for business valuation using the Discounted Cash Flow method. Along a theoretical framework covering the essentials of financial planning, business valuation, and the principles of Monte Carlo simulations, the practical implementation of these theories is demonstrated through a case study that conducts a sample valuation using various probability distributions to model uncertainties in financial forecasting. The thesis investigates how different choices of input parameters and their respective probability distributions influence the outcome of the business valuation. It emphasises the critical nature of accurately calibrating inputs to achieve reliable valuation results and highlights the potential risks associated with simulations. While Monte Carlo simulations can provide valuable insights and a robust framework for understanding the range of possible valuation outcomes, the reliability of these outcomes heavily depends on the correct assumptions and calibration of simulation inputs. Missteps in these areas can lead to significantly skewed results, underscoring the importance of rigorous verification and validation of simulation parameters in financial modelling.
Vedoucí práce: František Poborský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses